Dose implications of X-ray beam alignment in some radiological facilities in Abuja, Nigeria - Charles Unomieta; Samson D. Yusuf; Ibrahim Umar; Idris M. Mustapha (Universitas Sebelas Maret, 2024)
In this study, the percentage misalignment of X-ray beam and patient radiation dose of chest X-ray examination in radiographic X-ray equipment in some selected centres in Abuja were investigated. Beam alignment test was carried out in order to determine the working status and possible contribution to population radiation dose. The tools used were the beam alignment and collimator test tool Model 161A and Model 161B respectively. A total of four functional X-ray machines in four radio-diagnostic centres labelled in code for ethical reasons were recruited for the study. Results indicate that the beam alignment test conducted, 50% shows positive misalignment beyond the normal limit of 2% while 50% shows beam alignment within the normal limit. The percentage misalignment value ranged from 1.6% to 3.4% and 1.4% to 2.6% across and along the cassette respectively. Entrance Skin Dose (ESD) was calculated for patients undergoing chest X-ray examination in two selected diagnostic centres and was found 273.1 µGy and 491.6 µGy which appears to be lower and higher respectively to the recommended limit by international regulatory bodies. Increase in patients’ radiation dose is expected due to the beam misalignment in most of the diagnostic centre studied. It is therefore recommended that regulatory agencies should monitor compliance with quality assurance tests in all radio-diagnostic centres in Abuja.